Six Sigma Based Management Approach to Minimize Material Losses in Building Construction - Chancasanampa Narvaez, Kevyn Wyll; Cueva Villaverde, Jhon Brayam; Delzo Chihuan , Elizabeth; Arteaga Rojas, Jhonatan Seeler A. (Salehan Institute of Higher Education, 2026)
This study aims to reduce material variability, minimize losses, and improve construction performance in multifamily building projects by applying the Six Sigma DMAIC methodology in a Peruvian regional context. The research was conducted in Huancayo using a multifamily structure as a reference to compare theoretical material consumption with actual quantities registered on site. The methodological approach combined statistical analysis with Minitab, logistics modelling with Arena Simulation, data processing through Excel and Power Query, and real-time monitoring using Google Colab connected to Telegram. The analysis identified overconsumption patterns between six and nine percent in concrete, steel, and bricks, which contributed to an estimated delay of about thirty days. After implementing the DMAIC stages, cost deviations were reduced to ten percent or less, schedule performance improved by twelve percent, and operational efficiency reached ninety percent, with ninety-five percent of deliveries made on time. The study introduces a hybrid digital control framework that links Telegram with Google Colab and Power BI, allowing real-time tracking of key performance indicators in projects with limited budgets and low technology adoption. The findings provide one of the first documented applications of Six Sigma for material control in regional Peruvian construction and contribute to the adaptation of Lean Six Sigma principles to the Latin American context by offering practical, field-based evidence of their effectiveness.